Métodos de resolução de sistemas lineares - AQUINO , Marco Aurélio Silva de (2021)
This work presents methods of solving linear systems going back to their origins, addressing their historical development. For that, the substitution methods, Cramer's rule through determinants, scaling method and inverse matrix method will be contemplated.